Empowering Coastal Communities through a Feasibility Study of Lobster Cultivation in Central Buton Regency - Lina, Ismi Rizqa; Fauziyah, Nida Nurlivi; Damayanthy, Dessy (Asosiasi Profesi Multimedia Indonesia, 2026)
Background: Central Buton Regency has significant coastal and marine potential to support the development of lobster aquaculture using floating net cages (KJA). Favorable oceanographic conditions and available coastal space provides strong opportunities for expanding this high-value fisheries sector. However, large-scale development faces sustainability challenges, particularly related to feed supply and ecosystem management.Aims: This paper aims to assess the feasibility and development direction of lobster aquaculture in Central Buton Regency. The scope covers environmental suitability, initial production conditions, planned expansion to 500 floating net cages, and sustainable feed management strategies based on local resources.Methods: Field surveys were conducted on 12–14 December 2025 to observe farming locations and engage with lobster farmers. This was followed by a Focus Group Discussion (FGD) on 15 December 2025 involving village leaders, farmers, relevant stakeholders, and three invited experts to discuss the industry ecosystems, local farming techniques, and integrated feed management.Results: The results indicate that current feed demand can still be met using natural feed sources such as trash fish and shellfish. However, under the projected expansion to 500 floating net cages, daily feed requirements are estimated at approximately 5.5 tons for wet feed or 1.5 tons for pellet feed.Conclusion: Lobster aquaculture development in Central Buton Regency is technically feasible but requires integrated feed management planning. The development of shellfish farming and locally produced pellet feed is essential to ensure sustainability, reduce dependence on wild resources, and enhance long-term competitiveness. As a follow-up, this program encourages the establishment of a sustainable mentoring model for farmers in feed management and strengthening their data-based production capacity.